Cost Benefit Analysis for Feasibility of Waste Management Scenario (Case Study of Ganet Landfill, Tanjungpinang City) - Vitasari, Vitasari; Khodijah Ismail; Tengku Said Raza’i (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
The increase in the number and activities of the population will be in line with the increase in waste generation, resulting in an increase in the burden on the Ganet landfill. The current controlled landfill method can no longer manage the increasing waste load. A more efficient waste management design system is needed to minimize and prevent potential environmental damage. Waste management scenarios are designed based on the potential for waste processing at the Ganet landfill. In selecting waste management scenarios, an economic analysis is required, which is key in designing an effective waste management system. Cost Benefit Analysis (CBA) is used as an economic assessment of the 4 scenarios designed, namely scenario 0 (controlled landfill), scenario 1 (utilization by scavengers, composting and controlled landfill), scenario 2 (utilization by scavengers, composting, pyrolysis and controlled landfill) and scenario 3 (utilization by scavengers, composting, pyrolysis, paving block making and controlled landfill). The cost and benefit components were identified for each waste treatment process. The waste processing that costs the most is controlled landfill in scenario 0 amounting to IDR 8,326,123,157.87, while the waste processing process that produces the greatest benefit value is the manufacture of paving blocks amounting to IDR 158,392,662.33. The results of the Cost Benefit Analysis calculation show a Benefit Cost Rasio (BCR) value of 1.91, Net Present Value (NPV) of 8,448,737,857.40 and the fastest Payback Period (PP) of 5 months is scenario 3. This shows that the scenario is economically feasible to do. The results of this study are expected to be a consideration in the policy formulation related to waste management at the Ganet landfill.